Exploring Knowledge, Attitudes and Barriers among Postgraduate Distance Learners in India - Joshi, K.M.; Ahir, Kinjal; Priya, Ashutosh; Bhatta, Dharma Dev (Community College Research Journal, 2025)
This cross-sectional study explored the understanding and perspective of postgraduate students in distance education regarding research, along with the research barriers. The study aimed to compare the knowledge, attitudes, and challenges faced by students across different genders, four age groups, and three fields. A self-report questionnaire was administered to postgraduate students of distance education across three universities in Western India. Questions were primarily closed-ended and consisted of Likert scales. Descriptive statistics, independent sample t-test, and one-way ANOVA were used to analyse and compare the means of groups by gender, age, and field of study while using Excel and Jamovi. The study considered a 95 percent confidence level and the standard significance level p-value of 0.05 for statistical analysis. The study results showed that there was no statistically significant difference in the average knowledge and attitude scores of male and female students toward research. Additionally, there was no significant variance in the knowledge and attitude scores within different age groups and fields. The study revealed an above-average positive attitude towards research. The findings indicated that there was no significant difference in the score of barriers to research between male and female students, different age groups, and fields of postgraduate students of distance education. The major obstacles to involvement in research in distance education were found to be the unavailability of time, mentors, and social and family obligations.